2021
DOI: 10.1039/d1cy01897c
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of phenol via in situ H2O2 production over supported Pd-based catalysts

Abstract: The oxidative degradation of phenol via in situ H2O2 production offers an attractive route to the destruction of organic contaminants in water streams, overcoming the significant concerns associated with traditional water remediation technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Although in recent years great strides have been made in improving catalyst selectivity through the incorporation of numerous secondary metals into supported Pd catalysts. Perhaps most extensively studied has been the enhancement in catalytic efficacy through the alloying of Pd with Au, [8][9][10][11][12] however numerous investigations have demonstrated that the addition of a range of abundant metals including Fe, 13,14 Sn, 15,16 Ni, 17,18 In, 19 Ag, 20 Zn, 21,22 Te 23 and Co 24 can similarly enhance catalytic performance. Further studies have focussed on the incorporation of dopant levels of precious metals, in particular Pt, into supported Pd, [25][26][27][28] Au 29 and AuPd catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although in recent years great strides have been made in improving catalyst selectivity through the incorporation of numerous secondary metals into supported Pd catalysts. Perhaps most extensively studied has been the enhancement in catalytic efficacy through the alloying of Pd with Au, [8][9][10][11][12] however numerous investigations have demonstrated that the addition of a range of abundant metals including Fe, 13,14 Sn, 15,16 Ni, 17,18 In, 19 Ag, 20 Zn, 21,22 Te 23 and Co 24 can similarly enhance catalytic performance. Further studies have focussed on the incorporation of dopant levels of precious metals, in particular Pt, into supported Pd, [25][26][27][28] Au 29 and AuPd catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] Indeed, we have previously reported significant Fe leaching (>45%) during the oxidative degradation of phenol, under identical reaction conditions, when utilising a PdFe/TiO 2 catalyst, with the presence of the further phenol oxidation products identified to be key in catalysing metal leaching. 17,18 Analysis of post reaction solutions via microwave plasma atomic emission spectroscopy (MP-AES) (Table S4 †) reveals a significant improvement in catalyst stability compared to our earlier works and clearly demonstrates the key role of the zeolite support in inhibiting metal loss, this is despite the much greater selectivity of the zeolite based catalysts to species known to promote metal leaching. 19 We attribute the improved stability of the Pd/Fe-ZSM-5 catalysts studied within Catalysis Science & Technology Paper this work, in comparrison to those previously studied for the oxidative degradation of phenol, to the incorporation of large quantities of Fe into the zeoltitic framework.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 77%
“…Indeed, while numerous studies have identified the ability of supported Pd surfaces to catalyse the hydrogenation of phenol, temperatures far exceeding those used within the work are typically required 37 and we have previously ruled out this route to phenol conversion under identical reaction conditions. 18 The catalytic selectivity of Pd-based catalysts toward H 2 O 2 is known to be highly dependent on the oxidation state of Pd, with Pd 0 species typically more active toward both the direct synthesis and subsequent degradation of H 2 O 2 than analogous Pd 2+ materials. 38 Analysis of the Pd-based catalysts via X-ray photoelectron spectroscopy (XPS) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50)), to exhibit NO adsorption (Al-rich beta zeolites 51 and MOFs 52 ), to reduce NO and N 2 O (zeolites Fe-BEA [53][54][55][56] and Fe-beta 57 ) and to decompose N 2 O (zeolites Fe-FER, Fe-BEA and Fe-MFI 58,59 ). Another commonly used zeolite is Fe/ZSM-5, which has been investigated to produce olefins from methanol, 60 degrade phenol with the direct synthesis of H 2 O 2 , [61][62][63] a process which can also occur in Febeta. 64 Fe/ZSM-5 has also been employed together with FeHBEA and FeHMOR to assess the potential for decomposition 65 and formation 66 of N 2 O and for the selective catalytic reduction (SCR) of NO.…”
Section: Introductionmentioning
confidence: 99%